FENOMENA META, SINERGI 3 PLATFORM MEDIA SOSIAL: FENOMENA META, SINERGI 3 PLATFORM MEDIA SOSIAL - Ifa Safira Mustikadara Sagir; Faisal Irfansyah Moenggah (Wimba : Jurnal Komunikasi Visual, 2023)
MetaPlatform Inc. started with Facebook in 2004 and expanded after taking over Instagram, WhatsApp, Beluga and Oculus VR. This article reviews why and how Meta Platform Inc. developed Facebook, then took over and developed other platforms that make global social media play a significant role in various aspects of users' lives. Social media users, in various age groups have their own preferences in making choices to use their social media platforms. In this study, the authors limit it to 4 social media platforms, all of which are owned by Meta Platform Inc., namely: Facebook, Messenger, Instagram and Whatsapp, and their effects on users in the middle age group (40-60 years). Text analysis and user behavior in interacting and participating in using and following the dynamics of the four platforms. The results of this study show that the middle-aged generation tends to use primary features on the platform. Key features like photo sharing, text messaging and social interaction remain the main attraction for users in this age group.